THE EFFECTIVENESS OF USING THE DISCOVERY LEARNING MODEL BY USING WORDWALL ON STUDENTS' MOTIVATION IN ENGLISH SUBJECTS IN SMA PGRI 2 JOMBANG - Agustina, Ulfa Wulan; Mukhlisoh, Nani; Rahmawati, Ifa Yuni (Universitas Labuhanbatu, 2024)
This study aims to know the effectiveness of the Discovery Learning model by using Wordwall on students' motivation in English subjects. This study used Pre- Experimental Research and also used one-group pre-test and post-test designs. This study has seven steps, those are population, sample, pre-test, treatment, post-test, data processing, and conclusion. The population of this study was students of SMA PGRI 2 Jombang and the students of social sciences as an accessible population. Then, the sample in this study was the students of eleven grade class 4 with a total was 34 students. The result of the pre-test through questionnaires given to the students indicated that the student’s motivation in learning English was 58%. The result from the treatment step through the observation instrument was some information that many students were enthusiastic about learning English by using Wordwall. Next, the post- test through questionnaires showed that the student’s motivation to learn English was higher than before with a percentage of 73%. The conclusion was the result of the research suitable to the hypothesis was that the implemented discovery learning model by using Wordwall media can increase students' learning motivation in English subjects.